Precipitation-driven metastability engineering of carbon-doped CoCrFeNiMo medium-entropy alloys at cryogenic temperature - Kwon, Hyeonseok; Moon, Jongun; Bae, Jae Wung; Park, Jeong Min; Son, Sujung; Do, Hyeon-Seok; Lee, Byeong-Joo; Kim, Hyoung Seop (Scripta materialia, 2020)
Here, novel medium-entropy alloys with chemical compositions of Co17.5Cr12.5Fe55Ni10Mo4C1 and Co17.5Cr12.5Fe55Ni10Mo3C2 (at%) exhibiting excellent tensile properties at both room and liquid nitrogen temperatures have been developed. Precipitation of carbides changes the chemical composition and phase stability of the matrix, resulting in the controlled deformation-induced martensitic transformation from face-centered cubic to body-centered cubic of the alloys. The carbide precipitation, lattice distortion, and martensitic transformation led the alloy to have ultra-high yield strength of ~1 GPa and ultimate tensile strength of ~2 GPa with extra work hardening at liquid nitrogen temperature. [Display omitted]